Determination of trends of labor migration in the implementation of the Sustainable Development Goal - Taraniuk, Leonid; Taraniuk, Karina; Korsakiene, Renata; Miceikienė, Astrida; Demikhov, Oleksii (Technology audit and production reserves, 2025)
In the context of sustainable development of labor resources, the processes of labor migration are becoming increasingly widespread across the world, influencing the implementation of Sustainable Development Goal No. 8: Decent Work and Economic Growth. The object of the study is the bibliometric framework of scientific works by authors who research labor migration processes in the context of the implementation of the Sustainable Development Goals. The problem addressed in the study lies in the insufficient examination of labor migration issues with a specific focus on the implementation of the Sustainable Development Goals, as well as the need to identify current trends in scientific thought regarding labor migration processes within the framework of achieving the Sustainable Development Goals No. 8: Decent Work and Economic Growth. This problem was addressed through the analysis of scholarly works by authors studying labor migration processes, with particular attention to research directions categorized by specific bibliometric indicators. The study of factors influencing the implementation of Sustainable Development Goal No. 8: Decent Work and Economic Growth – such as the outflow of migrants from countries with a low living index and the increase in the inflow of labor migrants to countries with a higher living index – justifies the selection of this particular Goal for research. The essence of the results obtained is to determine labor migration trends within the framework of implementing the Sustainable Development Goal, which includes the substantiation of labor migration through the use of bibliometric metrics: by authors (by documents – 1; link strength range 1–7), by keywords (event range 5–103; link strength range 49–209), by citation of scientific works (link range 6–13; citation range 1–262), and by the geographical factor of scientific schools (link strength range 9–67; citation range 78–3140). This explains the formation of a bibliometric field of scientific thought regarding labor migration within the implementation of Sustainable Development Goal No. 8: Decent Work and Economic Growth. Regarding the practical implementation of the obtained research results, they can be applied in the formation of modern topics in the field of labor migration when developing project proposals for scientific, educational, and international grants.